New Raman–visible near‐infrared database of inorganic and mineralogical planetary and terrestrial compounds and its implications for Mars: Phyllosilicates. (18th July 2019) - Ruiz‐Galende, Patricia; Torre‐Fdez, Imanol; Aramendia, Julene; Gomez‐Nubla, Leticia; Castro, Kepa; Arana, Gorka; de Vallejuelo, Silvia Fdez‐Ortiz; Maguregui, Maite; Medina, Jesús; Baonza, Valentín G.; Rull, Fernando; Madariaga, Juan Manuel
Abstract: The European Space Agency will launch the ExoMars Martian mission in 2020, which will study traces of water activity through the geological history of Mars, as water would mean potential presence of life. In this sense, silicates, and more concretely phyllosilicates, are among the most relevant mineral phases to be studied on the Martian surface at Oxia Planum, the selected landing site. Phyllosilicates are widely spread over the planet, together with sulfates and carbonates, in places where liquid water seems to have been present, and, therefore, knowledge about their mineralogy is of high importance. Thus, the creation of Raman and visible near‐infrared (VNIR) mineralogical databases can be critical for the interpretation of both the terrestrial analogues and the upcoming data from Mars, as Raman and VNIR spectroscopies will be on board the rovers of the ExoMars as well as of the NASA Mars 2020 missions to Mars. For that purpose, several phyllosilicates of the collection of the Geominery Museum of the Spanish Geological and Miner Institute were characterized geochemically to be used as reference. A wide number Raman and VNIR spectra of common and rare phyllosilicates were collected, and several of these are presented here. Abstract : The creation of spectroscopic databases becomes crucial for the proper interpretation of both terrestrial analogues and the upcoming data from Mars. In this work, Raman and visible near‐infrared spectroscopies were used as they will be on board the rover of the ExoMars mission. Phyllosilicates are among the most relevant mineral phases to be studied because they need the presence of water for their formation. For that purpose, several phyllosilicates were analysed for their characterization and to use as reference.